Gender pay gap in American CFOs: Theory and evidence - Francis, Bill B.; Hasan, Iftekhar; Hovakimian, Gayane; Sharma, Zenu (Journal of Corporate Finance, 2023)
Studies document persistent unexplained gender-based wage gap in labor markets. At the executive level, where skill and education are similar, career interruptions and differences in risk preferences primarily explain the extant gender-based pay gap. This study focuses on CFO compensation contracts of Execucomp firms (1992–2020) and finds no gender-based pay gap. This paper offers several explanations for this phenomenon, such as novel evidence on the risk preferences of females with financial expertise and changes in the social and regulatory climate.